Aspek Biologi Udang Jerbung (Penaeus merguiensis de Man 1888) di Perairan Kabupaten Teluk Bintun, Papua Barat - Pranata, Bayu; Kusuma, Aradea Bujana; Sala, Ridwan; Sabariah, Vera; Lapadi, Ida; Saleh, Fitriyah Irnawati E.; Wyrasti, Andi Fajeriani; Kolibongso, Duaitd (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2025)
The waters of Bintuni Bay have abundant natural resources, especially aquatic biota. One of the aquatic biota with high economic value is the Jerbung shrimp (Penaeus merguiensis). Currently, information about the biological aspects of shrimp in the waters of Bintuni Bay is still very lacking. Specifically, the aim of this research is to examine the size structure, first caught size (L50%), infinity size (L∞), growth patterns, condition factors and gonad maturity level (TKG) of Jerbung shrimp in the waters of Bintuni Bay. The research method used is the survey method. The research was carried out from March to April 2023. The results showed that the average carapace length and weight of male shrimp were 4.6 cm and 14.8 gr. Meanwhile, the average shell length and weight of female shrimp are 5.4 cm and 25.8 grams. The L50% value of male and female shrimp is 5.3 cm and 5.8 cm, the ½ L∞ value of male and female shrimp is 3.4 cm and 3.5 cm. If L50% > ½ L∞ means the size of the shrimp caught is quite large. The growth pattern of male and female shrimp is negative allometry (b = 0.1035 and b = 0.7424). The condition factor values for male and female shrimp are 0.31 and 1.73. The results of TKG observations showed that 75.2% of female shrimp were in TKG I and II, meaning that 50% of the shrimp caught had not yet reached TGK III and IV at the time of the research.